Prospective study of sexual dysfunction after proctectomy for rectal cancer - YEGEN, ŞEVKET CUMHUR (ELSEVIER SINGAPORE PTE LTD, 2018)
Background: Although rectal cancer is a common malignancy and has an improved cure rate in response to oncological treatment, research on rectal-cancer survivors' sexual function remains limited. Objective: The aim of this prospective study is to assess sexual dysfunction after rectal cancer surgery. Patients and methods: Patients undergoing curative rectal cancer surgery were included in the study. Sexual function before and 6 months after the operation was measured using the validated questionnaires. Primary outcome was to determine the rates of Sexual dysfunction after rectal cancer surgery. Furthermore, the factors which can have an impact on sexual function after radical treatment have been assessed. Results: A total of 187 patients [117 (63%) men and 70 (37%) women] with rectal cancer who underwent radical resection were included in the study. Sexual function has significantly decreased after surgery. Among male patients, sexual dysfunction increased from the baseline 4% (n = 5) up to 41% (n = 48) after the operation. Among female patients, sexual dysfunction increased from the baseline 53% (n = 37) up to 77% (n = 54) after the operation. A significant lower rate of laparoscopic surgery has been found in both males and females who reported sexual dysfunction after surgery. The patients who have locally advanced disease and those who received postoperative chemotherapy or radiotherapy have higher rates of sexual dysfunction. Conclusion: This study, showed that sexual dysfunction is common in patients with rectal cancer after radical treatment. However, patients who underwent laparoscopic surgery have lower rates of sexual dysfunction than those who underwent open surgery. (C) 2017 Asian Surgical Association and Taiwan Robotic Surgical Association. Publishing services by Elsevier B.V.
Keywords: Rectal cancer; Sexual dysfunction; Proctectomy; QUALITY-OF-LIFE; TOTAL MESORECTAL EXCISION; PREOPERATIVE RADIOTHERAPY; MULTIMODALITY THERAPY; ERECTILE DYSFUNCTION; ANTERIOR RESECTION; SURGERY; BLADDER; TRIAL; SILDENAFIL